Zro2 pre-sintered blocks (3%mol-y2o3) with color gradient for dental prostheses - de Freitas, Rodrigo Xavier; Dos Santos, Claudinei; de Freitas, Bruno Xavier; Simba, Bruno Galvão [UNESP] (Trans Tech Publications, 2018)
In dentistry, metal-free ceramic systems are used to improve optical properties in dental restorations. Ceramics based on tetragonal zirconia ZrO2-Y2O3 are used in the manufacturing of dental prostheses for being biocompatible and for presenting proper mechanical and optical properties. Most of tetragonal zirconia blocks are commercialized in one only hue, which difficult the achievement of high aesthetic performance due to the tooth’s polychromatic characteristics. This work proposes to obtain tetragonal zirconia blocks fabricated by uniaxial cold pressing in different hues which could provide ceramic prostheses with better aesthetic results in less time. Zirconia blocks in two different colors were produced and characterized for their physical properties and mechanical resistance. The colors difference between the layers was obtained by using different amounts of Fe2 O3. Ceramics with relative density superior to 99% were obtained by sintering the materials at 1530ºC for 120 minutes. The mechanical properties evaluated indicated hardness close to 1270HV and fracture toughness of 7MPa.m1/2. Blocks with different hues may be an alternative in order to favor the aesthetics in the cervical region and decrease the amount of ceramic veneering.
Keywords: CAD/CAM prototyping; Characterization; Color; Dental ceramics; ZrO2(Y2O3)